Response of growth and production of rice varieties caused by application amendment straw Bokashi and specific location of fertilization in salin soil - Rini Sulistiani; Dini Mufriah (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Efforts to improve rice tolerance to salt stress conditions to obtain salinity tolerant varieties can be done through adaptation of anatomy and morphology. Research was conducted in Paluh Ketuk, Kecamatan Percut Sei Tuan. The experiment was using factorial randomized block design with two factors.The first factor is Amendment (A) consists of 4 degrees: 0 t/ha, 4 t/ha, 8 t/ha and 12 t/ha. The second factor is the Varieties (V) consists of 6 kinds: Ciherang, Bestari, Inpari 4, Mekongga, Inpari 13 and Cibogo. The variables are: leaf area, number of tillers, number of productive tillers, number of grains per panicle,number of chlorophyll, 1000 grain weight and grain weight/ plot. Data were analyzed by F test and Duncan Multiple Range Test (DMRT), further analysis by response curve. The yield of higher in order are Bestari, Ciherang and Mekongga. Compost treatments were significant in variable of leaf area and grain weight per plot. Whereas the varieties treatments were significant on number of tillers, number of productive tillers, number of grains per panic and grain weight per plot. Combination treatments of compost and varieties were significant on grain weight per plot. Rice varieties suggested are Bestari, Ciherang and Mekongga its tend to have better resistance to higher grain yield than other varieties.